2016
DOI: 10.1007/s10068-016-0160-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a modified QuEChERS method coupled with LC-MS/MS to determine arbutin in pear peels

Abstract: A new effective method was developed to determine the concentration of arbutin in pear peels using a modified QuEChERS (Quick, Easy, Cheap, Effective, Rugged, and Safe) method and liquid chromatography-tandem mass spectrometry (LC-MS/MS). The original QuEChERS was modified to enable the extraction of the polar arbutin molecule. Use of an initial 50:50 acetonitrile:water extraction solvent led to the highest extraction efficiency. The arbutin extracted from pear peels was found to be identical to the β-arbutin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Next, the developed LC-MS method based on [d 4 ]-arbutin as an IS was used to detect arbutin in Brigitta (0.43 ± 0.01 lg/mg of dry weight, DW) and Duke (0.40 ± 0.01 lg/mg of DW) blueberry leaves, as well as strawberry leaves (0.16 ± 0.02 lg/mg of fresh weight, FW) and pear peels (6.86 ± 1.39 lg/mg of DW). The results from these measurements were in agreement with previous studies, which report the concentrations of arbutin in blueberry leaves and pear peels to be 0.35 ± 0.01 lg/ mg of DW and in the range of 0.92-27.70 lg/mg of DW, respectively [17,35,36]. To the best of our knowledge, the concentration of arbutin in strawberry leaves (Fragaria spp.)…”
Section: Methods Validation Using Lc-mssupporting
confidence: 92%
“…Next, the developed LC-MS method based on [d 4 ]-arbutin as an IS was used to detect arbutin in Brigitta (0.43 ± 0.01 lg/mg of dry weight, DW) and Duke (0.40 ± 0.01 lg/mg of DW) blueberry leaves, as well as strawberry leaves (0.16 ± 0.02 lg/mg of fresh weight, FW) and pear peels (6.86 ± 1.39 lg/mg of DW). The results from these measurements were in agreement with previous studies, which report the concentrations of arbutin in blueberry leaves and pear peels to be 0.35 ± 0.01 lg/ mg of DW and in the range of 0.92-27.70 lg/mg of DW, respectively [17,35,36]. To the best of our knowledge, the concentration of arbutin in strawberry leaves (Fragaria spp.)…”
Section: Methods Validation Using Lc-mssupporting
confidence: 92%
“…A total of 300 peaks were detected in the chromatogram. By comparing the m/z values, the RTand the fragmentation patterns with the MS 2 spectral data taken from the literature [2,17,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] or to search the data bases (MS2T, MassBank, HMDB). 78 metabolites were putatively identified as phenols, aromatic compounds, phenyl alkanoids, flavonoids, monoterpenoids, acyclic alcohol glycosides, anthocyanins etc.…”
Section: Resultsmentioning
confidence: 99%
“…Exposures to DEHP, BBP, DBP, and DEP are associated with dermatitis, conjunctivitis, and allergic symptoms [47]. Other studies have found a relationship of asthma and worsening of pulmonary functions with these phthalates [48].…”
Section: Quantification Of Phthalates In Plastic-based Food Packagingmentioning
confidence: 99%